Experimental setup for anisotropic thermoelectric transport measurements using MPMS. (11th January 2019) - Tripathi, Tripurari S; Karppinen, Maarit
Abstract: At reduced dimensions the electrical transport properties of materials often depend on the measurement direction. Here we report on a measurement setup designed on the manual insertion utility probe (MIUP) of the Quantum Design's magnetic property measurement system (MPMS) to measure anisotropic transport properties in the temperature range of 10–400 K and magnetic fields up to 5 Tesla. The setup is capable of measuring the Seebeck coefficient and electrical resistivity both along and perpendicular to the applied magnetic field. The Seebeck measurement is based on the differential measurement technique; the four-probe electrical resistivity measurement can easily be performed on the opposite side of the setup. The setup consists of a small copper cube (5  ×  5  ×  5 mm 3 ) fitted with diagonally cut electrically insulated square strips. The strips are fitted with copper-constantan thermocouple in differential arrangement for the temperature-gradient (Δ T ) measurement and symmetrically arranged surface mount (SM) resistors to create the Δ T across the sample. The cube can be rotated to alter the direction of the applied magnetic field on the sample. We demonstrate the directional dependence of the measured transport properties for a normal platinum wire and for single crystal flakes of CuCr2 Se4 .